Electric measurement of ultra-high dilutions—a blinded controlled experiment - Walach, Harald; Asseldonk, Tedje Van; Bourkas, Pericles; Delinick, Alexandra; Ives, Galen; Karragiannopoulos, Costas; Lüdtke, Rainer; Wassenhoven, Michel van; Witt, Claudia (British Homeopathic Journal, 1998)
This experiment was designed to test the hypothesis put forward by P. Bourkas, A. Delinick and C. Karragiannopoulos of the National Technical University of Athens (NTUA) that Ultra High Succussed Dilutions (UHSD) can be distinguished from control solutions by an Electric Measurement Device (EMD), developed by the NTUA team. A pre-formulated experimental protocol was followed, measuring in random sequence test solutions of double-distilled and deionised water (aqua injectabile), potentised water (6 cH, 30 cH), Natrum muriaticum (Nat mur) potentised in aqua injectabile (6 cH, 30 cH), either blind or open. The number of measurements was determined by a power analysis based on open pilot readings. While the open pilot trial performed by the NTUA team showed a large difference in readings for the controls and test-solutions, the experimental blind test was negative. The only significant difference observed was between Nat mur 6 cH and Nat mur 30 cH, and the direction of the difference was in the opposite direction from that predicted by theory and found in the pilot experiment. No differences were found between any other conditions, and in particular Nat mur 30 cH and aqua 30 cH could not be distinguished. It was suggested that the failure to detect a difference in the main trial resulted from a different brand of water being used in the main trial; the likelihood of this, and other alternative explanations, is discussed. It was concluded that the EMD is a highly sensitive apparatus for measuring impurities in water. As yet there is no obvious link between the measurement of impurities in water and the purported alteration of solvent in the process of homoeopathic potentisation.